Mobile augmented reality learning: design exploration toward student learning trends - Kassim, Mohd Hisyammudin; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Abdullah, Fadzidah (American Scientific Publishers, 2018)
The advancement of educational technologies and students learning trends have forced the educationist to adapt a new innovative learning method in disseminating learning content. This approach inspired the research to explore the Mobile Learning (mLearning) platform designed specifically for architectural history education via Augmented Reality (AR) app. Throughout the research, the researchers highlight the mLearning platform’s theory, potential, requirements as well as challenges in responding to students learning trends. The research objectives are; First, to investigate the students learning trends in utilizing educational technology infrastructures available at the higher education institution. Second, to explore the development of Mobile Augmented Reality Learning Platform toward learning experiences. The qualitative approach is applied which involved exploratory literature reviews, expert interviews and document analysis for formative evaluation. The reflection promises a new way of students learning experience by enhancing the traditional learning method via Mobile Augmented Reality Learning Platform.